MANDATORY COVID-19 VACCINATIONS AT UNIVERSITIES IN SOUTH AFRICA: GUIDANCE FROM THE UNITED STATES AND THE EUROPEAN UNION - Franaaz Khan; Kirstin Hagglund (Obiter, 2023)
During the past two decades, immunisation has saved millions of lives and prevented countless illnesses and disabilities in South Africa. Vaccination is the most important thing we can do to protect ourselves and our children against ill health. Vaccinations prevent up to three million deaths worldwide every year. However, the World Health Organization (WHO) has listed vaccine hesitancy as one of the biggest threats to global health. Vaccine hesitancy entails people with access to vaccines delaying or refusing vaccination. In addition to vaccine hesitancy, many people are of the view that it infringes on their fundamental human right to bodily integrity. However, this article presents findings that suggest that this right can be limited because everyone has a fundamental right to be protected from the spread of the disease. Tensions have increased as more vaccine mandates are implemented. Businesses continue to review and revise their Covid-19 vaccination policies as new mutations emerge and employers may be asking what they can do if workers refuse to get the jab. Some employers have dismissed employees or put them on unpaid leave. Others have required unvaccinated employees to submit to weekly testing and take other safety precautions. In terms of the Code of Practice: Managing Exposure to SARS-COV-2 in the Workplace, 2022, the identifiable hazard relating to Covid-19 that workers face is the transmission of virus by an infectious person to others in the workplace. The Regulations for Hazardous Biological Agents, 2022 lists SARS-COV-2 as a hazardous biological agent that places legal responsibilities on employers to mitigate the associated risks. Each situation requires special measures to be implemented by employers in order to prevent the transmission of the virus. Universities in South Africa are also faced with this conundrum regarding the mandating of vaccines. This article examines and discusses mandating vaccines in South Africa, especially at universities, with guidance received from international instruments such as the European Union and countries such as United States. Various legislative and policy frameworks are also analysed.